Governing blockchain in Africa: Regulatory capacity, fragmented authority, and digital sovereignty - Kudakwashe Zhou; Thomas Sheku Marah (Privietlab, 2026)
Blockchain technology is transforming financial governance and regulatory authority across Africa. However, existing scholarship often treats blockchain either as a developmental tool or as a technical and regulatory problem. This article argues that such approaches overlook the way decentralized digital infrastructures reconfigure the institutional distribution of governance authority. Drawing on a qualitative comparative analysis of blockchain governance frameworks in Nigeria, Kenya, and South Africa between 2017 and 2025, this study examines how African states regulate decentralized financial technologies under conditions of fragmented authority, uneven regulatory capacity, and technological dependency. Using regulatory governance theory and digital sovereignty scholarship, the analysis demonstrates that blockchain governance increasingly operates through polycentric regulatory arrangements involving state institutions, private technological actors, and transnational financial infrastructures. This article advances governance scholarship by conceptualizing digital sovereignty not primarily as territorial control over digital space but as the capacity to exercise infrastructural and regulatory authority within decentralized technological ecosystems.